Infection risks associated with daratumumab-containing regimens in multiple myeloma: a systematic review and meta-analysis - Huang, Zeng-Yi; Liu, Xiao-Lian; Li, Ting; Luo, Chao-Han (Frontiers in Oncology, 2026)
Daratumumab, a CD38-targeting monoclonal antibody, is a key component of therapy for both newly diagnosed and relapsed or refractory multiple myeloma. By depleting CD38-expressing immune effector cells and reducing immunoglobulin levels, daratumumab may increase susceptibility to infections. To quantify this risk, we performed a systematic review and meta-analysis of randomized phase II and III trials comparing daratumumab-containing regimens with standard therapies in adults with multiple myeloma. Databases including PubMed, Embase, Web of Science, the Cochrane Library, and ClinicalTrials.gov were searched through 14 October 2025, following PRISMA 2020 guidelines. Nine trials encompassing 5,281 patients were included. Daratumumab-based regimens were associated with an increased risk of any infection (risk ratio [RR] 1.23; 95% confidence interval [CI] 1.14–1.33), grade ≥3 infection (RR 1.29; 95% CI 1.17–1.42), and pneumonia (RR 1.60; 95% CI 1.24–2.07). Subgroup analyses showed consistent results across disease stages and transplant eligibility groups. Infection-related mortality was uncommon (≤2%) and did not differ significantly between arms. These findings indicate that daratumumab-based therapy increases infection risk, particularly for severe infections and pneumonia, but the absolute mortality remains low. Proactive infection prevention and close clinical monitoring are warranted as the use of daratumumab continues to expand. This study was prospectively registered in PROSPERO (CRD420251165266).Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/, CRD420251165266.